An ultra-low attenuation optical fiber and a method for manufacturing the same

CN122940360APending Publication Date: 2026-10-20YANGTZE OPTICAL FIBRE & CABLE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611134355.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-29
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

[0006]本发明通过提供一种超低衰减光纤及其制备方法,解决现有技术中碱金属掺杂工艺的控制精度较差、难以实现高浓度掺杂的问题

Benefits of technology

本发明首先配制KNO3与NaNO3的二元共晶混合盐,其中,KNO3的质量分数为45%至65%,NaNO3的质量分数为35%至55%;然后利用载气携带液态的二元共晶混合盐表面的钾蒸汽,并通入至反应管中;利用钾蒸汽与原料气体反应生成碱金属氧化物,并沉积在芯层玻璃中;最后将完成沉积的反应管塌缩成实心棒,并在形成包层后进行拉丝,得到超低衰减光纤。本发明配制的二元共晶混合盐的共晶熔点最低可至约 220℃左右,相对于现有方案进行碱金属元素掺杂时采用的熔点极高的卤盐(例如,KCl的熔点高达770℃,KBr的熔点高达在734℃),本发明无需如现有方案那样将蒸发源加热到800℃甚至更高的温度,因此本发明可避免现有方案因采用高温蒸发工艺而存在的弊端,可以实现高浓度掺杂并改善掺杂均匀性,能够保证沿着棒长轴向碱金属含量的均匀性,进而能够保证衰减的均匀性。本发明采用Na、K两种碱金属盐共掺,由于Na的原子半径小,K的原子半径大,二者扩散系数不一样,因此可有效增加芯层的碱金属平均浓度,进而降低假想温度,从而降低光纤的损耗。综上,本发明提出了一种全新的碱金属掺杂工艺,能够在较低的温度下实现稳定、精准的钾元素掺杂,突破了现有工艺的限制,并制备出了衰减均匀性好、衰减更低的光纤。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention belongs to the field of optical communication technology and discloses an ultra-low attenuation optical fiber and its fabrication method. The invention first prepares a binary eutectic mixed salt of KNO3 and NaNO3, wherein the mass fraction of KNO3 is 45% to 65% and the mass fraction of NaNO3 is 35% to 55%. Then, a carrier gas carries potassium vapor from the surface of the liquid binary eutectic mixed salt and introduces it into a reaction tube. The potassium vapor reacts with the raw material gas to generate alkali metal oxides, which are deposited in the core glass. Finally, the completed reaction tube is collapsed into a solid rod, and after cladding formation, it is drawn into fiber to obtain the ultra-low attenuation optical fiber. This invention proposes a novel alkali metal doping process that enables stable and precise potassium doping at lower temperatures, breaking through the limitations of existing processes and producing optical fibers with good attenuation uniformity and lower attenuation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of optical communication technology, and more specifically, relates to an ultra-low attenuation optical fiber and its preparation method. Background Technology

[0002] With the rapid development of 5G, cloud computing, and submarine optical cable communication systems, optical transmission networks are placing increasingly stringent demands on the attenuation performance of optical fibers. The attenuation coefficient of an optical fiber directly determines the transmission distance of the optical signal and the relay cost of the system. Research shows that the inherent loss of optical fibers mainly originates from Rayleigh scattering, and the magnitude of Rayleigh scattering is closely related to the density fluctuations during the freezing process of glass. This physical quantity is usually expressed as the fictitious temperature (T0). f The hypothetical temperature is used to characterize the glass. A lower hypothetical temperature means the glass structure is closer to thermodynamic equilibrium, with smaller density fluctuations and lower Rayleigh scattering. To lower the hypothetical temperature, current techniques typically dope the core layer with alkali metal elements (such as potassium (K) and sodium (Na)). Alkali metal ions, acting as network modifiers, can break Si-O-Si bridging oxygen bonds, significantly reducing the high-temperature viscosity of the glass. This not only makes the viscosity of the core layer and the fluorine-doped cladding more closely matched at the drawing temperature, reducing interfacial stress, but more importantly, the reduced viscosity promotes structural relaxation of the glass network during cooling, thus effectively lowering the hypothetical freezing temperature.

[0003] However, the doping of alkali metal elements has always been a challenge in the process. In traditional MCVD (Modified Chemical Vapor Deposition) or PCVD (Plasma Chemical Vapor Deposition) processes, the commonly used potassium sources are mainly potassium chloride (KCl) or potassium bromide (KBr). These conventional halides have extremely high melting points; for example, KCl has a melting point as high as 770℃, and KBr is at 734℃. In order to vaporize them and generate doped vapor, the evaporation source must be heated to 800℃ or even higher. This high-temperature evaporation process has the following significant drawbacks: (1) Poor control precision: At high temperatures, the saturated vapor pressure of solid salts is extremely sensitive to temperature. Small temperature fluctuations (±5℃) can cause drastic changes in the evaporation rate, resulting in large fluctuations in the alkali metal doping concentration along the length of the preform, making it difficult to ensure the uniformity of doping throughout the entire rod. (2) Difficulty in achieving high concentration doping: Due to the extremely rapid and difficult-to-control volatilization of salts at high temperatures, the process window is extremely narrow. To prevent excessive doping from causing crystallization or bubble defects, the doping concentration is usually limited in the process, typically only a few tens of ppm, which limits further reduction of the hypothetical temperature.

[0004] Although some alternatives have been proposed in the existing technology, such as the solution immersion method, which involves immersing the porous preform in a potassium salt solution, this method suffers from problems such as difficulty in dehydration, easy introduction of hydroxyl (OH) impurities leading to increased water peak loss, and uneven distribution of doped ions, making it difficult to meet the stringent requirements of ultra-low loss optical fibers.

[0005] Therefore, there is an urgent need in this field to develop a new alkali metal doping process to achieve stable and precise potassium doping at lower temperatures, thereby breaking through the limitations of existing processes and producing optical fibers with lower attenuation. Summary of the Invention

[0006] This invention provides an ultra-low attenuation optical fiber and its fabrication method, thereby solving the problems of poor control precision and difficulty in achieving high concentration doping in the existing alkali metal doping process.

[0007] This invention provides a method for fabricating ultra-low attenuation optical fiber, comprising the following steps: Prepare a binary eutectic mixed salt of potassium nitrate (KNO3) and sodium nitrate (NaNO3), wherein the mass fraction of KNO3 is 45% to 65% and the mass fraction of NaNO3 is 35% to 55%. A carrier gas is used to carry potassium vapor from the surface of a liquid binary eutectic mixed salt and introduce it into a reaction tube; the potassium vapor reacts with the raw material gas to generate alkali metal oxides, which are then deposited in the core glass. The reaction tube after deposition is collapsed into a solid rod, and after the cladding is formed, it is drawn into a fiber to obtain an ultra-low attenuation optical fiber.

[0008] Preferably, when preparing the binary eutectic mixed salt, the mass fraction of KNO3 is 50% to 60% and the mass fraction of NaNO3 is 40% to 50%.

[0009] Preferably, when preparing the binary eutectic mixed salt, KNO3 and NaNO3 with a purity of not less than 99.999% and in powder form are first dried and cooled to room temperature, and then KNO3 and NaNO3 are mixed evenly by dry powder mixing.

[0010] Preferably, the prepared binary eutectic mixed salt is placed in a sealed storage tank, and the temperature of the storage tank is kept constant at 220°C to 250°C. At this temperature, the binary eutectic mixed salt remains in a stable liquid state and has a stable saturated vapor pressure. The carrier gas is introduced into the storage tank to carry the potassium vapor on the surface of the liquid binary eutectic mixed salt.

[0011] Preferably, the flow rate of the carrier gas is controlled by a mass flow controller to regulate the input rate of the potassium vapor; the carrier gas is helium (He) or oxygen (O2).

[0012] Preferably, the raw material gas includes silicon chloride (SiCl4) and germanium chloride (GeCl4).

[0013] Preferably, the deposition process further includes doping by introducing a fluorine-containing gas; the core layer of the ultra-low attenuation fiber is co-doped with germanium, fluorine and alkali metal, and the average content of alkali metal in the core layer is 250 ppm to 350 ppm; the cladding of the ultra-low attenuation fiber is a fluorine-doped layer.

[0014] Preferably, the attenuation coefficient of the ultra-low attenuation optical fiber at a wavelength of 1550nm is no greater than 0.151dB / km, and the difference in attenuation coefficient is no greater than 0.01dB / km.

[0015] Preferably, the effective area of ​​the ultra-low attenuation optical fiber at a wavelength of 1550 nm is 110 μm. 2 Up to 150μm 2 The cutoff wavelength for cabling of the ultra-low attenuation optical fiber is no greater than 1530nm.

[0016] On the other hand, the present invention provides an ultra-low attenuation optical fiber, which is prepared by the above-described method for preparing ultra-low attenuation optical fibers.

[0017] One or more technical solutions provided in this invention have at least the following technical effects or advantages: This invention first prepares a binary eutectic mixed salt of KNO3 and NaNO3, wherein the mass fraction of KNO3 is 45% to 65% and the mass fraction of NaNO3 is 35% to 55%. Then, a carrier gas is used to carry potassium vapor from the surface of the liquid binary eutectic mixed salt and introduce it into a reaction tube. The potassium vapor reacts with the raw material gas to generate alkali metal oxides, which are deposited in the core glass. Finally, the reaction tube after deposition is collapsed into a solid rod, and after the cladding is formed, it is drawn into fibers to obtain ultra-low attenuation optical fiber. The binary eutectic mixed salt prepared in this invention has a eutectic melting point as low as approximately 220°C. Compared to existing methods that use extremely high-melting-point halides for alkali metal doping (e.g., KCl has a melting point as high as 770°C, and KBr has a melting point as high as 734°C), this invention eliminates the need to heat the evaporation source to 800°C or even higher temperatures as in existing methods. Therefore, this invention avoids the drawbacks of existing methods that rely on high-temperature evaporation processes, enabling high-concentration doping and improved doping uniformity. It ensures the uniformity of alkali metal content along the rod length axis, thereby guaranteeing attenuation uniformity. This invention uses co-doping with two alkali metal salts, Na and K. Due to the small atomic radius of Na and the large atomic radius of K, their diffusion coefficients are different, effectively increasing the average alkali metal concentration in the core layer, thereby reducing the hypothetical temperature and thus reducing fiber loss. In summary, this invention proposes a novel alkali metal doping process that achieves stable and precise potassium doping at lower temperatures, breaking through the limitations of existing processes and producing optical fibers with good attenuation uniformity and lower attenuation. Attached Figure Description

[0018] Figure 1 This is a schematic diagram of alkali metal doping in a method for preparing an ultra-low attenuation optical fiber provided by the present invention. Detailed Implementation

[0019] To better understand the above technical solutions, the following will provide a detailed explanation of the technical solutions in conjunction with the accompanying drawings and specific implementation methods.

[0020] The first aspect of this invention provides a method for fabricating ultra-low attenuation optical fiber, mainly comprising the following steps: S1. Prepare a binary eutectic mixed salt of potassium nitrate (KNO3) and sodium nitrate (NaNO3), wherein the mass fraction of KNO3 is 45% to 65% and the mass fraction of NaNO3 is 35% to 55%.

[0021] In the preparation of the binary eutectic mixed salt, more preferably, the mass fraction of KNO3 is 50% to 60%, and the mass fraction of NaNO3 is 40% to 50%.

[0022] When preparing the binary eutectic mixed salt, KNO3 and NaNO3 with a purity of not less than 99.999% and in powder form can be dried separately (for example, dried at 120°C for 2 hours) and cooled to room temperature. Then, KNO3 and NaNO3 can be mixed evenly by dry powder mixing.

[0023] That is, step S1 is to prepare a low-melting-point alkali metal salt source. The eutectic melting point of the binary eutectic mixed salt prepared by this invention can be as low as about 220°C.

[0024] S2. A carrier gas is used to carry potassium vapor from the surface of a liquid binary eutectic mixed salt and introduce it into a reaction tube; the potassium vapor reacts with the raw material gas to generate alkali metal oxides, which are then deposited in the core glass.

[0025] For details, see Figure 1 The prepared binary eutectic mixed salt can be placed in a sealed storage tank, and the temperature of the storage tank is constantly controlled at 220℃ to 250℃. At this temperature, the binary eutectic mixed salt remains in a stable liquid state and has a stable saturated vapor pressure. This operation can avoid the instability of traditional solid salt sublimation at high temperatures, ensure the uniformity of alkali metal content along the rod length axis, and thus ensure the uniformity of decay. The inner layer of the storage tank is quartz, the outer layer is wrapped with an armored electric heating belt, and the middle is filled with aluminum silicate insulation cotton, which can achieve uniform heating, avoid molten salt solidification caused by local temperature differences, and maintain the temperature at 220℃ to 250℃.

[0026] The carrier gas is then introduced into the storage tank to carry potassium vapor from the surface of the liquid binary eutectic mixed salt. A high-precision mass flow controller can be used to control the flow rate of the carrier gas, thereby regulating the input rate of the potassium vapor and achieving closed-loop control of the doping concentration at the ppm level. The carrier gas can be helium (He) or oxygen (O2), preferably oxygen, with a flow rate of 2.5 SLM to 3 SLM.

[0027] During the core deposition stage of the MCVD process, a carrier gas carrying alkali metal vapor is introduced into a quartz reaction tube. The potassium vapor and the feed gas undergo an oxidation reaction under the action of a high-temperature flame, generating alkali metal oxides which are uniformly deposited in the core glass. The feed gas can be silicon chloride (SiCl4), germanium chloride (GeCl4), etc. Furthermore, to prevent alkali metal condensation, the temperature can be maintained above 220°C using a heating system in the reaction pipeline.

[0028] In addition, the deposition process also includes doping with fluorine-containing gas.

[0029] That is, step S2 includes several core components: constructing a precise gasification system, carrier gas carrying and precise delivery, and MCVD deposition and doping.

[0030] S3. The reaction tube after deposition is collapsed into a solid rod, and after the cladding is formed, it is drawn into a fiber to obtain an ultra-low attenuation optical fiber.

[0031] Because the high concentration of alkali metal ions in the core layer reduces the glass viscosity, the glass network is sufficiently relaxed during the drawing and cooling process, effectively lowering the hypothetical temperature. The drawing speed is between 1000 m / min and 2000 m / min.

[0032] The core layer of the finally prepared ultra-low attenuation optical fiber is co-doped with germanium, fluorine and alkali metal, and the average content of alkali metal in the core layer is 250 ppm to 350 ppm. The cladding of the ultra-low attenuation optical fiber is a fluorine-doped layer.

[0033] That is, step S3 is sintering and wire drawing.

[0034] The ultra-low attenuation optical fiber prepared by the above method has an attenuation coefficient of no more than 0.151 dB / km at a wavelength of 1550 nm, and an attenuation coefficient difference of no more than 0.01 dB / km. Under preferred conditions, the ultra-low attenuation optical fiber has an attenuation coefficient of no more than 0.147 dB / km at a wavelength of 1550 nm.

[0035] The ultra-low attenuation optical fiber has an effective area of ​​110 μm at a wavelength of 1550 nm. 2 Up to 150μm 2 The cutoff wavelength for cabling of the ultra-low attenuation optical fiber is no greater than 1530nm.

[0036] In other words, this invention provides a method for preparing ultra-low attenuation optical fibers based on low-melting-point alkali metal salts, which can solve the problems of high evaporation temperature, poor control precision, and difficulty in achieving high concentration doping of traditional high-melting-point potassium halide salts. This invention can achieve high-precision and high-concentration alkali metal doping, which can minimize the hypothetical temperature and transmission attenuation of the optical fiber, and finally obtain an optical fiber with good attenuation uniformity and lower attenuation.

[0037] A second aspect of this invention provides an ultra-low attenuation optical fiber, which is prepared using the method for preparing ultra-low attenuation optical fibers as provided in the first aspect of this invention. The ultra-low attenuation optical fiber includes a core layer and a cladding layer; the core layer is co-doped with germanium (Ge), fluorine (F), and an alkali metal, and the cladding layer is entirely fluorine-doped.

[0038] The core layer contains an average alkali metal content of 250 ppm to 350 ppm. The core layer can be doped with a high concentration of germanium by MCVD deposition. For example, the germanium content in the core layer is about 25,000 ppm. In addition, the fluorine content in the core layer can be about 4,000 ppm.

[0039] The present invention will be further described below with reference to embodiments (including embodiments 1 to 4) and comparative examples.

[0040] In Example 1, the prepared binary eutectic mixed salt contained 57% KNO3 and 43% NaNO3 by mass. The melting point of the alkali metal source was 219°C.

[0041] In Example 2, the prepared binary eutectic mixed salt contained 65% KNO3 and 35% NaNO3 by mass. The melting point of the alkali metal source was 236°C.

[0042] In Example 3, the prepared binary eutectic mixed salt contained 45% KNO3 and 55% NaNO3 by mass. The melting point of the alkali metal source was 245°C.

[0043] In Example 4, the prepared binary eutectic mixed salt contained 52% KNO3 and 48% NaNO3 by mass. The melting point of the alkali metal source was 225°C.

[0044] In the comparative example, a commonly used potassium source, potassium bromide (KBr), was used. In this comparative example, the melting point of the alkali metal source was 734℃.

[0045] The process parameters and performance data of the above embodiments and comparative examples are shown in Table 1.

[0046] Table 1. Process parameters and performance data for the examples and comparative examples.

[0047] As can be seen from Table 1, the melting points of the alkali metal sources in Examples 1 to 4 are significantly lower than those in the comparative example. The optical fibers in Examples 1 to 4 exhibit superior attenuation performance, with attenuation coefficients at 1550 nm all not exceeding 0.151 dB / km, and attenuation coefficient differences not exceeding 0.01 dB / km (see Table 1). Figure 1 The attenuation coefficient difference between the air end, middle, and tail end is 0), and the attenuation uniformity is significantly better than the comparative example. Examples 1 and 4, as preferred solutions, also show significantly better attenuation coefficients than the comparative example. In particular, Example 1 has an attenuation coefficient of only 0.147 dB / km, a reduction of up to 0.006 dB / km compared to the comparative example. For this level of ultra-low attenuation fiber, this reduction is substantial.

[0048] In summary, this invention proposes a novel alkali metal doping process that enables stable and precise potassium doping at lower temperatures, overcoming the limitations of existing processes and producing optical fibers with good attenuation uniformity and lower attenuation.

[0049] Finally, it should be noted that the above specific embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.

Claims

1. A method for fabricating ultra-low attenuation optical fiber, characterized in that, Includes the following steps: Prepare a binary eutectic mixed salt of potassium nitrate (KNO3) and sodium nitrate (NaNO3), wherein the mass fraction of KNO3 is 45% to 65% and the mass fraction of NaNO3 is 35% to 55%. A carrier gas is used to carry potassium vapor from the surface of a liquid binary eutectic mixed salt and introduce it into a reaction tube; the potassium vapor reacts with the raw material gas to generate alkali metal oxides, which are then deposited in the core glass. The reaction tube after deposition is collapsed into a solid rod, and after the cladding is formed, it is drawn into a fiber to obtain an ultra-low attenuation optical fiber.

2. The method for fabricating ultra-low attenuation optical fiber according to claim 1, characterized in that, When preparing the binary eutectic mixed salt, the mass fraction of KNO3 used is 50% to 60%, and the mass fraction of NaNO3 is 40% to 50%.

3. The method for fabricating ultra-low attenuation optical fiber according to claim 1, characterized in that, When preparing the binary eutectic mixed salt, KNO3 and NaNO3 with a purity of not less than 99.999% and in powder form are first dried and cooled to room temperature, and then KNO3 and NaNO3 are mixed evenly by dry powder mixing.

4. The method for fabricating ultra-low attenuation optical fiber according to claim 1, characterized in that, The prepared binary eutectic mixed salt is placed into a sealed storage tank, and the temperature of the storage tank is kept constant at 220°C to 250°C. At this temperature, the binary eutectic mixed salt remains in a stable liquid state and has a stable saturated vapor pressure. The carrier gas is introduced into the storage tank to carry the potassium vapor on the surface of the liquid binary eutectic mixed salt.

5. The method for fabricating ultra-low attenuation optical fiber according to claim 1, characterized in that, The flow rate of the carrier gas is controlled by a mass flow controller to regulate the input rate of the potassium vapor; the carrier gas is either helium (He) or oxygen (O2).

6. The method for fabricating ultra-low attenuation optical fiber according to claim 1, characterized in that, The raw material gas includes silicon chloride (SiCl4) and germanium chloride (GeCl4).

7. The method for fabricating ultra-low attenuation optical fiber according to claim 1, characterized in that, The deposition process also includes doping with fluorine-containing gas; the core layer of the ultra-low attenuation fiber is co-doped with germanium, fluorine and alkali metal, and the average content of alkali metal in the core layer is 250 ppm to 350 ppm; the cladding of the ultra-low attenuation fiber is a fluorine-doped layer.

8. The method for fabricating ultra-low attenuation optical fiber according to claim 1, characterized in that, The ultra-low attenuation optical fiber has an attenuation coefficient of no more than 0.151 dB / km at a wavelength of 1550 nm, and an attenuation coefficient difference of no more than 0.01 dB / km.

9. The method for fabricating ultra-low attenuation optical fiber according to claim 1, characterized in that, The ultra-low attenuation optical fiber has an effective area of ​​110 μm at a wavelength of 1550 nm. 2 Up to 150μm 2 The cutoff wavelength for cabling of the ultra-low attenuation optical fiber is no greater than 1530nm.

10. An ultra-low attenuation optical fiber, characterized in that, It is prepared using the method described in any one of claims 1 to 9 for the preparation of ultra-low attenuation optical fiber.